Impact of Irradiation on m-Nitroacetanilide in Presence of a Photocatalyst - Joshi, J.D.; Vora, Jabali; Sharma, Sangita; C. Patel, Chirag; Brahmbhatt, M.P.; B. Patel, Ashok (Asian Journal of Chemistry, 2016)
The irradiated semiconductor catalyzed degradation of m-nitroacetanilide on zinc oxide powder was carried out. The decomposition of the substrate was observed to be affected by photocatalytic characteristics. The effect of variation of different parameters like concentration of substrate, pH, amount of the semiconductor, light intensity and sensitizer on the rate of photocatalytic degradation was observed. Probable mechanism for the photocatalytic degradation of m-nitroacetanilide is proposed.